Information service identity generation and management scheme for service supervision - Xiang LI; Hao WANG; Qiange LIU; Chao WANG; Jian MAO; Jianwei LIU (网络与信息安全学报)
While information services have a significant impact on economic and social development, it also brings a series of security challenges.Realizing fine-grained, continuous, and dynamic supervision of information services has become the top priority of information service management.Traditional static identity authentication and management mechanisms, are difficult to meet the continuous monitoring requirements for information service entities and service quality.An information service identification generation and management scheme for service supervision was proposed.It defined an information service identification format from multiple perspectives such as information service category, service grade, and service quality credibility.It used the analytic hierarchy process to evaluate information services and designed a dynamic management of information service identification.The scheme can meet the needs of issuance and fine-grained dynamic management of information service identification for multi-dimensional business attributes.